Tough Materials Through Ionic Interactions - Salminen, Linda; Karjalainen, Erno; Aseyev, Vladimir; Tenhu, Heikki (Frontiers in Chemistry, 2021)
This article introduces butyl acrylate-based materials that are toughened with dynamic crosslinkers. These dynamic crosslinkers are salts where both the anion and cation polymerize. The ion pairs between the polymerized anions and cations form dynamic crosslinks that break and reform under deformation. Chemical crosslinker was used to bring shape stability. The extent of dynamic and chemical crosslinking was related to the mechanical and thermal properties of the materials. Furthermore, the dependence of the material properties on different dynamic crosslinkers—tributyl-(4-vinylbenzyl)ammonium sulfopropyl acrylate (C4ASA) and trihexyl-(4-vinylbenzyl)ammonium sulfopropyl acrylate (C6ASA)—was studied. The materials’ mechanical and thermal properties were characterized by means of tensile tests, dynamic mechanical analysis, differential scanning calorimetry, and thermogravimetric analysis. The dynamic crosslinks strengthened the materials considerably. Chemical crosslinks decreased the elasticity of the materials but did not significantly affect their strength. Comparison of the two ionic crosslinkers revealed that changing the crosslinker from C4ASA to C6ASA results in more elastic, but slightly weaker materials. In conclusion, dynamic crosslinks provide substantial enhancement of mechanical properties of the materials. This is a unique approach that is utilizable for a wide variety of polymer materials.